Assessment of menopausal symptoms using modified Menopause Rating Scale (MRS) among middle age women in Kuching, Sarawak, Malaysia - Syed Alwi, S.A.R; Siti Rubiah, Zainuddin; Lee, Verna Kar Mun (https://link.springer.com/article/10.1186/1447-056X-9-5, 2010)
Abstract Background: Menopausal symptoms can be assessed by several tools, and can be influenced by various sociodemographic factors. Objectives: To determine the commonly reported menopausal symptoms among Sarawakian women using a modified Menopause Rating Scale (MRS). Methods: By using modified MRS questionnaire, 356 Sarawakian women aged 40-65 years were interview to document of 11 symptoms (divided into somatic, psychological and urogenital domain) commonly associated with menopause. Results: The mean age of menopause was 51.3 years (range 47 - 56 years). The most prevalent symptoms reported were joint and muscular discomfort (80.1%); physical and mental exhaustion (67.1%); and sleeping problems (52.2%). Followed by symptoms of hot flushes and sweating (41.6%); irritability (37.9%); dryness of vagina (37.9%); anxiety (36.5%); depressive mood (32.6%). Other complaints noted were sexual problem (30.9%); bladder problem (13.8%) and heart discomfort (18.3%). Perimenopausal women (n = 141) experienced higher prevalence of somatic and psychological symptoms compared to premenopausal (n = 82) and postmenopausal (n = 133) women. However urogenital symptoms mostly occur in the postmenopausal group of women. Conclusions: The prevalence of menopausal symptoms using modified MRS in this study correspond to other studies on Asian women however the prevalence of classical menopausal symptoms of hot flushes, sweating was lower compared to studies on Caucasian women.